Board characteristics and financial performance: evidence from Bursa Malaysia Financial Times Stock Exchange (FTSE) top 100 index firms - Nur Hafizah Abdul Puhat,; Suhaily Hasnan,; Khairul Ayuni Mohd Kharuddin,; Hafizah Marzuki,; Mazurina Mohd Ali, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Research on the relationship between corporate governance and firm financial performance in Malaysia is inconclusive, and only covers the period before the implementation of Malaysian Code on Corporate Governance (MCCG) 2017. Therefore, this study examines the relationship between corporate governance and the financial performance of 80 non-financial firms listed on the Financial Times Stock Exchange (FTSE)Bursa Malaysia Top 100 Index between the years of 2018 and 2020. The descriptive statistics reveal that on average, the 23% composition of female directors on the board is still below the recommended MCCG 2017 and 2021 threshold of 30%. The small percentage of politically-connected directors (19%) and military-experienced directors (5%) reported in this study can be viewed favourably in line with the recent MCCG 2021 recommendation that the appointment of the directors should be apolitical or politically neutral without having any executive powers in politics. In addition, the multiple regression results indicate that board size and board meeting frequency are negatively related to firm financial performance. Female directors show a positive and significant relationship with firm financial performance. However, the effects of board independence, board alumni, board financial expertise, politically-connected directors, and military-experienced directors on firm financial performance, are insignificant. This study is beneficial to academicians, policymaker/regulators, and firm managers, in considering the contributions of corporate governance mechanisms to large listed companies’ financial performance, particularly in an emerging market.